Glitches in the utilization of telehealth in pediatric rheumatology patients during the COVID-19 pandemic - Nayimisha Balmuri; Karen B. Onel (BMC, 2020)
Abstract Telehealth is an extraordinary advancement of modern medicine. It has increased access to care for underserved populations and, in the case of pediatric rheumatology, has expanded the reach of a limited work force. During the Coronavirus Disease 2019 (COVID-19) pandemic, telehealth has radically changed the way healthcare workers have been able to deliver care while maintaining social distance. In addition to the infectious havoc of COVID-19, the pandemic has further altered the psychosocial milleu of our society which directly impacts the wellness and safety of our pediatric rheumatology patients. These psychosocial factors may be difficult to assess and triage solely using telehealth. The objective of this short review is to educate practitioners on the psychosocial concerns exacerbated by the COVID-19 pandemic and to discuss the possible hurdles in utilization of telehealth to care for our vulnerable patient population.